2018
DOI: 10.5539/ijel.v8n7p83
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse in Students’ Academic Writing: Case Study of Umaru Musa Yar’adua University and Al-Qalam University Katsina

Abstract: Studies on writing, thus, become crucial because when students make the transition from Secondary School to a Tertiary Institution, they encounter many challenges. One of them is the writing of B.A projects. Most of these undergraduate students both in L1 (English as a first language) and L2 (English as a second language) still find it difficult to argue, discuss or evaluate competently as well as persuasively in English essay writing. The present study aimed at exploring metadiscoursal choice and its influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The findings of the analysis show that most writers make greater use of metadiscourse in their article introductions. In contrast, Haruna et al (2018), in their research, the findings show that many of the students are not exposed to the elements of metadiscourse markers; thus, they write academic essays the way they speak. Duruk (2017) has an in-depth analysis that explores the use of interpersonal metadiscourse markers used by Turkish writers in the written register and the way Turkish writers use metadiscourse, namely in MA dissertations from one major academic field; English Language Teaching (ELT).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The findings of the analysis show that most writers make greater use of metadiscourse in their article introductions. In contrast, Haruna et al (2018), in their research, the findings show that many of the students are not exposed to the elements of metadiscourse markers; thus, they write academic essays the way they speak. Duruk (2017) has an in-depth analysis that explores the use of interpersonal metadiscourse markers used by Turkish writers in the written register and the way Turkish writers use metadiscourse, namely in MA dissertations from one major academic field; English Language Teaching (ELT).…”
Section: Introductionmentioning
confidence: 82%
“…Studying metadiscourse markers (MDMs) is extended by several researchers. The studies focus on persuasive writings or speech produced in a number of different contexts such as academic research articles (Ozdemir & Longo, 2014;Massaabi, 2014;Kawase, 2015;Haruna et al, 2018;Davoodi, 2016;Duruk, 2017;Ahour & Maleki, 2014;Zareifard & Alinezhad, 2014;Jiang & Hyland, 2016;Mina & Biria, 2017), speeches (Wong & Yap, 2015;Malmström, 2016;Esmer, 2017;Gholami & Ilghami, 2016;Gordon & Luke, 2016;Mahmoodian & Simin, 2017;Sukma, 2017), media discourse (Sukma & Sujatna, 2014;Dafouz-Milne, 2008), business discourse (Ho, 2018;Fu, 2012), and translation (Gholami, Tajalli, & Shokrpour, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the findings of previous studies, like that of Tan (2011) who observed that many second language writers experience difficulties in using Metadiscourse in their writing activities. Similarly, Haruna, Ibrahim, Haruna, Ibrahim and Yunus (2018) affirmed that many Nigerian undergraduates were not exposed to the Metadiscourse and their importance in writing, this led the students to write the way they speak.…”
Section: Frequency Of the Metadiscourse Usedmentioning
confidence: 99%
“…Few studies were conducted to investigate the use of metadiscourse devices in the writing of Nigerian undergraduates (Haruna, Ibrahim, Haruna, Ibrahim & Yunus, 2018). However, there seems to be an absence of studies that specifically investigates the use of metadiscourse in persuasive writing or compare the use of metadiscourse and the quality of the students' writing.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, there have been limited studies that have explored the use of metadiscourse among university students. However, Haruna et al (2018) conducted a study examining the metadiscoursal choice and its influence on the success of final year undergraduates' academic writing, where they found that many of the students did not use or wrongly used the devices. Additionally, Akinseye (2021) examined the metadiscursive markers in L2 PhD theses abstracts of five disciplines in Nigerian university and showed the predominance of interactive metadiscourse markers across the disciplines.…”
Section: Previous Studies On Metadiscoursementioning
confidence: 99%